Agro costing methodology: concepts, definitions and applicability - Bassotto, Leandro Carvalho; de Benedicto, Gideon Carvalho; Lima, André Luis Ribeiro; Lopes, Marcos Aurélio [UNESP]; Nascimento, Esteffany Francisca Reis (My University, 2022)
The Theory of the Firm (subdivided into Theory of Production, Costs and Income) allows analyzing the performance of organizations and tracing a connection between market interferences on their productive performance. Indeed, this theory becomes fundamental for cost management in rural properties, justified by the relevance of the theme to the context of national agriculture. The objective of this research was to propose a cost methodology linked to the Theory of the Firm that can be applied in agriculture and contribute to the cost management of rural properties. In order to reach the proposed objective, a bibliographical review was carried out in the literature about the Theory of the Firm and the main cost methodologies used in agriculture and, with that, to establish a connection between the Theory of the Firm, much studied in Applied Social Sciences, with the areas of Agricultural Sciences and Animal Production. The Agro Costing Methodology proposes that costs be classified into cash (all out-of-pocket costs), total (out-of-pocket and non-out-of-pocket costs) and attractiveness (total cost and opportunity cost). Additionally, the parity point was used instead of the break-even point, which, as it is negative when the contribution margin is negative, makes it unfeasible to use in properties where variable costs are greater than unit revenue. The Custeio Agro methodology proved to be efficient to determine production costs on agricultural properties with producers with different needs. Furthermore, it established distinctions between concepts such as financial, accounting and economic costs. Furthermore, this research contributes to the advancement of scientific knowledge by establishing a multidisciplinary connection in different areas of knowledge.
Metodologia do custeio agro: conceitos, definições e aplicabilidade
Keywords: Costs management; Production cost; Theory of the Firm